2022
DOI: 10.1111/jcmm.17237
|View full text |Cite
|
Sign up to set email alerts
|

CD93 in macrophages: A novel target for atherosclerotic plaque imaging?

Abstract: Noninvasive imaging atherosclerotic (AS) plaque is of great importance for early diagnosis. Recently, CD93 in MΦ was linked to atherosclerosis development. Herein, we have investigated whether CD93 in MΦ is a potential novel target for atherosclerotic plaque imaging. CD93hi and CD93lo MΦ were prepared with or without LPS stimulation, before biological activity was evaluated. A rat AS model was produced with left carotid artery clamped. Whole‐body/ex vivo phosphor autoradiography of the artery and biodistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…20,21 Chen Su showed that CD93 might be a potential new reporter for noninvasive atherosclerotic plaque imaging. 22 CD93 levels were significantly higher in asthmatics than in healthy controls, and inhibition of CD93 increased levels of the inflammatory cytokine IL-6. IL-6 and its receptor are present in human coronary atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 87%
“…20,21 Chen Su showed that CD93 might be a potential new reporter for noninvasive atherosclerotic plaque imaging. 22 CD93 levels were significantly higher in asthmatics than in healthy controls, and inhibition of CD93 increased levels of the inflammatory cytokine IL-6. IL-6 and its receptor are present in human coronary atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 87%
“…The expression of CD93 in monocytes and macrophages was associated with atherosclerosis in both animal and human studies [ 11 , 31 ]. Macrophages play a central role in the very first phases of atherosclerosis, regulating the inflammation levels in response to the lipid accumulation in the arterial tunica intima and phagocyting oxidised LDL particles and cholesterol crystals [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cx3cr1 and Ccr2 have been found to be associated with in ammatory progression in the liver [13][14]. Cd93 can exert a proin ammatory effect in atherosclerosis [15]. Gpnmb has been identi ed to have a bidirectional effect on in ammation [16].…”
Section: Characteristics and Biological Functions Of Lams Distributed...mentioning
confidence: 99%